Effect of The Composition of TiO2 Additives on The Physical and Magnetic Properties Crystal Structure and Microstructure of BaFe12O19 Magnetic Ceramics - Ramlan Ramlan; Endah Puspita (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
In this research, the manufacture of barium hexaferrite (BaFe12O19) magnetic ceramics and the addition of titanium dioxide (TiO2) additives with variations of 0%: 0.3%: 0.6% and 0.9% used the powder metallurgical method. The characterization used in this study is the measurement of density, porosity, X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Vibrating Sample Magnetometer (VSM), and Impulse Magnetizer K-Series. Based on the results of density and porosity measurements, the highest values were 4.95 g/cm3 and 5.45%, respectively. XRD results showed the formation of a BaFe12O19 phase with some impurities at 0% (Fe2O3), 0.3% and 0.9% (Ti6O11), and 0.6% (Ti4O7). The SEM results showed that the morphology of TiO2-BaFe12O19 was quite homogeneous, and the size and cavity ranged from 0.5 – 1.5 μm and 0.25 – 0.9 μm, respectively. VSM results show Mr, Ms, Hc, and Bhmax values of 1,489 kG, 3,235 kG, 1,758 kOe, and Bhmax of 0,867 MGOe, respectively. The results of the Impulse Magnetizer K-Series show the maximum and lowest magnetic flux values of 272.65 gauss and 218.10 gauss at 0.6% and 0% variation, respectively.